Effects of thyroxine on apoptosis and proliferation of mammary tumors. (1st December 2021) - Zyla, Leila E.; Cano, Rocio; Gómez, Silvina; Escudero, Alexa; Rey, Lara; Santiano, Flavia E.; Bruna, Flavia A.; Creydt, Virginia Pistone; Carón, Rubén W.; Fontana, Constanza López
Abstract: Hypothyroidism is a protective factor against breast cancer but long-term exposure or overdoses of thyroid replacement therapy with thyroxine (T4 ) may increase breast cancer risk. Objective: to study, in vivo and in vitro, the effects of T4 on the proliferation and apoptosis of mammary tumors of hypo- and euthyroid rats, and the possible mechanisms involved in these effects. Material and Methods: Female Sprague-Dawley rats were treated with a single dose of dimethylbenzathracene (15 mg/rat) at 55 days of age and were divided into three groups: hypothyroidism (HypoT; 0.01% 6-N-propyl-2-thiouracil -PTU- in drinking water, n = 20), hypothyroidism treated with T4 (HypoT + T4 ; 0.01% PTU in drinking water and 0.25 mg/kg/day T4 via sc; n = 20) and EUT (untreated control, n = 20). At sacrifice, tumor explants from HypoT and EUT rats were obtained and treated either with 10 −10  M T4 in DMEM/F12 without phenol red with 1% Charcoalized Fetal Bovine Serum or DMEM/F12 only for 15 min to evaluate intracellular signaling pathways associated with T4, and 24 h to evaluate changes in the expression of hormone receptors and proteins related to apoptosis and proliferation by immunohistochemistry and Western Blot. Results: In vivo, hypothyroidism retards mammary carcinogenesis but its treatment with T4 reverted the protective effects. In vitro, the proliferative and anti-apoptosis mechanisms of T4 were different regarding the thyroid status. In EUT tumors, the main signaling pathway involved was the cross-talk with other receptors, such as ERα, PgR, and HER2. In HypoT tumors, the non-genomic signaling pathway of T4 was the chief mechanism involved since αvβ3 integrin, HER2, β-catenin and, downstream, PI3K/AKT and ERK signaling pathways were activated. Conclusion: T4 can regulate mammary carcinogenesis by mainly activating its non-genomic signaling pathway and by interacting with other hormone or growth factor pathways endorsing that overdoses of thyroid replacement therapy with T4 can increase the risk of breast cancer. Highlights: Thyroxine treatment reverted the cancer-protective effects of hypothyroidism. Proliferative and antiapoptosis mechanisms of T4 varied regarding the thyroid status. The cross-talk with other hormone receptors was critical in EUT tumors. The non-genomic pathway of T4 was the main mechanism involved in HypoT tumors. Overdoses of T4 can increase breast cancer risk.